Tanggung Jawab Sosial Perusahaan Menuju Perbankan Berkelanjutan : Tinjauan Literatur - Tuti Setiatin; Niken Safitri; Rizal Zaelani; Ebah Suaebah; Muhammad Zaky (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2025)
Main Purpose - This research aims to understand the implementation and impact of Corporate Social Responsibility (CSR) on the financial performance, non-financial performance, and reputation of banks in several countries. Method - The method used was a literature review. The analysis was conducted on 17 journal articles in accordance with the predetermined inclusion criteria from the period 2019 to 2024. Main Findings - The research results indicate that CSR disclosure enhances the reputation and financial performance of banks, and attracts more investors. There is a positive relationship between CSR practices and financial performance, although the results vary. Involvement in CSR also improves risk management and employee loyalty. Theory and Practical Implications - Banks need to integrate CSR practices into their business strategies to improve performance. Policymakers are advised to encourage transparency in the disclosure of CSR information. Novelty - The novelty of this research lies in its emphasis on the importance of CSR in the banking sector to achieve sustainability and financial gains.